MEMBANGUN SISTEM PENDIDIKAN MULTIKULTURAL DI INDONESIA - Natalis Sukma Permana (Bahasa Indonesia, 2018)
Education is one of the elements of character building and human self-development. Education is expected to provide learning so that learners are able to understand themselves, others, the community environment and all the differences that exist in the environment and be tolerant to all the differences that exist in society. Multicultural education is expected to be one of the ways in which learners develop tolerant attitudes toward different racial, ethnic, social and cultural groups, religions, etc. According to UU No. 20 Year 2003 about the National Education System mentions "Education is conducted in a democratic and fair and non-discriminatory way by upholding human rights, religious values, cultural values, and national pluralism". From article 4 it can be concluded that multicultural education becomes one of the attention in the national education system in Indonesia. Through a multicultural education, learners are able to appreciate the diversity of cultural diversity that exists in Indonesia, increasing the spirit of tolerance to the differences given that the culture of Indonesian society is very diverse. Multicultural education is given to learners in the hope that they have the knowledge and understanding that in the country Indonesia is synonymous with plurality and prone to conflict. Multicultural education is expected to reduce the potential for conflict caused by various pluralism. Through the integration of curriculum and approaches in the learning process. In this case the school has a significant role in supporting the formation of a multicultural education society culture while the teacher also has a role in integrating and linking materials that lead to understanding and awareness of multiculturalism in Indonesia. Through multicultural education, learners are expected to have good competence, to behave and apply democratic values, humanism and pluralism in school and out of school. Thus, multicultural education system will be very possible to held with the cooperation of various parties that support the education process in Indonesia.